Numerical investigation of the failure mechanisms of soil–rock mixture slopes by material point method. (October 2022) - Zhao, Lianheng; Qiao, Nan; Huang, Dongliang; Zuo, Shi; Zhang, Zijian
Abstract: A new technique for establishing material point method (MPM) models of soil–rock mixture slopes was proposed to accurately analyze the large-deformation failure mechanisms of soil–rock mixture slopes. First, natural rock block contours were obtained through a digital image processing technique, followed by analyzing and reconstructing the rock block contours with the help of the discrete Fourier transform theory. Next, The discrete models of soil–rock mixture slopes for MPM were constructed by combining the stochastic placement algorithm with the digital image processing technique. Moreover, using the MPM, the influences of the content, the size, and morphology of rock blocks on the failure mechanisms of the slopes were investigated in detail. The results reveal that the content, features, and spatial distribution of rock blocks significantly influence the slope failure characteristics. Owing to the existence of rock blocks, the plastic zone of a slope at failure becomes heterogeneous and complex, showing multiple sliding regions and failure modes.